CRYPTOGRAPHIC TECHNIQUES FOR SECURE KEY MANAGEMENT IN PERSONNEL CLOUD - B, VEDIKA; Abdul Quadir (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Cloud computing has become an emerging model of IT industry as it can be accessed anywhere in the world on a pay-per-use basic. But, one major problem it is facing in today's challenging world is the security issues. Whenever the data is transferred through different connected networks, the threat is there for the users, that their data might get leaked from outsiders or an unauthorized people.In this paper we propose the solution for the above mentioned problem. We go through the cryptographic techniques by combining the two messages into an encrypted data and then sending it to the destination. We also propose a new method of how to exchange the keys and how the keys get interact at the user and system level.